INTEGRATING THE INDUAK SAMANG-ANAK SAMANG PHILOSOPHY INTO A PSYCHOEDUCATIONAL MODEL TO ENHANCE THE EMPLOYABILITY SKILLS OF VOCATIONAL SCHOOL STUDENTS - Elfira, Yenni; Neviyarni, Neviyarni; Afdal, Afdal (LPPM Universitas Jambi, 2026)
Vocational high school graduates in Indonesia face the highest unemployment rates, largely due to deficient employability skills. This study developed and validated the BIDASAN psychoeducational model a culturally responsive intervention rooted in the Minangkabau